Pengaruh Gaya Kepemimpinan Transformasional Dan Gaya Kepemimpinan Demokratis Terhadap Kinerja Karyawan (Studi Kasus Pada Gaperoma Malang) - Nurcahyo, Dwi; Hadiyati , Ernani (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to examine and analyze the simultaneous, partial, and dominant influence of transformational leadership style and democratic leadership style on the performance of GAPEROMA employees.This research uses a quantitative method. The population in this study consists of employees of the Gabungan Perusahaan Rokok Malang (GAPEROMA). The sample was selected using a representative sampling technique. In this study, the researcher used a saturated sampling technique, where the entire population is used as the sample. This is often applied when the total population is relatively small, less than 100 people. Data were collected through a questionnaire, which was first tested for validity and reliability. The data analysis technique used is multiple linear regression, preceded by classical assumption tests. Data were analyzed using SPSS software.The results of the study show that: i) Transformational and democratic leadership styles have a positive and significant simultaneous influence on employee performance at GAPEROMA; ii) Transformational and democratic leadership styles have a positive and significant partial influence on employee performance at GAPEROMA; iii) Transformational leadership style has a dominant influence on employee performance at GAPEROMA.